Unusual Coupling Reactions of Aldehydes and Alkynes: A Novel Preparation of Substituted Phthalic Acid Derivatives by Automated Synthesis - Jacobi von Wangelin, Axel; Neumann, Helfried; Gördes, Dirk; Klaus, Stefan; Jiao, Haijun; Spannenberg, Anke; Krüger, Thomas; Wendler, Christian; Thurow, Kerstin; Stoll, Norbert; Beller, Matthias (Chemistry : a European journal, 2003)
Based upon a highly versatile multicomponent methodology, a new one‐pot synthesis of substituted phthalic acid derivatives from α,β‐unsaturated aldehydes was developed. The reaction involves the intermediacy of an acetamidodiene species which undergoes Diels–Alder addition to diethyl acetylenedicarboxylate. The resultant acetamidocyclohexadiene is subject to elimination of acetamide under the reaction conditions to give rise to substituted diethyl phthalates in good yields. This domino condensation–cycloaddition–elimination sequence has been applied to a variety of α,β‐unsaturated aldehydes. Furthermore, we demonstrated the exploitation of parallelized and automated synthesis technology for the rapid screening of reaction conditions and compositions. Detailed studies revealed the catalytic role of the employed acetamide and the occurrence of a stereoselective 1,4‐syn elimination pathway under standard conditions. A new domino condensation –cycloaddition–elimination sequence for the synthesis of substituted phthalic esters has been developed and subjected to parallelized and automated. The 60‐well Syncore reactor used for the synthesis is depicted with the reaction scheme.